Engaging the Imagination: 'New Nature Writing', Collective Politics and the Environmental Crisis. (1st December 2018) - Oakley, Kate; Ward, Jonathan; Christie, Ian
Abstract : This paper explores the potential of 'new nature writing' - a literary genre currently popular in the UK - as a kind of arts activism, in particular in terms of how it might engage with the environmental crisis and lead to a kind of collective politics. We note the limitations of the genre, notably the reproduction of class, gender and ethnic hierarchies, the emphasis on nostalgia and loss, and the stress on individual responses rather than collective politics. But we also take seriously the claims of art to enable us to imagine other futures, suggesting that new nature writing has the potential to play a role in collective forms of environmental justice and capabilities.